2011
DOI: 10.1039/c1cp20335e
|View full text |Cite
|
Sign up to set email alerts
|

A bright, slow cryogenic molecular beam source for free radicals

Abstract: We demonstrate and characterize a cryogenic buffer gas-cooled molecular beam source capable of producing bright beams of free radicals and refractory species. Details of the beam properties (brightness, forward velocity distribution, transverse velocity spread, rotational and vibrational temperatures) are measured under varying conditions for the molecular species SrF. Under typical conditions we produce a beam of brightness 1.2×10 11 molecules/sr/pulse in the X 2 Σ + (v = 0, Nrot = 0) state, with 140 m s forw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
166
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(184 citation statements)
references
References 67 publications
(126 reference statements)
18
166
0
Order By: Relevance
“…We have found this to be better than using an ablation target formed from a mixture of powders. Lower energy ablation pulses can be used, the signal is more stable, and we do not observe much powdered residue building up in the cell, as reported by others (45,46), even after long periods of operation. It has been suggested that such particulates, or 'dust', might be responsible for reducing the lifetime of molecules in buffer gas cells (47).…”
Section: Construction Detailssupporting
confidence: 88%
See 1 more Smart Citation
“…We have found this to be better than using an ablation target formed from a mixture of powders. Lower energy ablation pulses can be used, the signal is more stable, and we do not observe much powdered residue building up in the cell, as reported by others (45,46), even after long periods of operation. It has been suggested that such particulates, or 'dust', might be responsible for reducing the lifetime of molecules in buffer gas cells (47).…”
Section: Construction Detailssupporting
confidence: 88%
“…This reduces the helium gas load into the rest of the system, and is similar to the design in reference (46). Installing it reduced the pressure measured outside the radiation shields by a factor of 2.…”
Section: Construction Detailsmentioning
confidence: 70%
“…This can be operated in the "hydrodynamically enhanced" regime or an "effusive" regime to yield bright slow beams of translationally cold molecules and radicals for cold collision experiments. The method has been demonstrated for cold beams of O 2 , 36 CaH, 37 SrF, 38 and benzonitrile. 39 Buffer gas cooled molecules have also been used as a continuous source of cold molecules for cavity-enhanced direct frequency comb spectroscopy 40 and enantiomer-specific detection of chiral molecules via microwave spectroscopy.…”
Section: A Methods For Creation Of Cold and Ultracold Moleculesmentioning
confidence: 99%
“…The limiting systematic errors in the measurement are sufficiently well understood that we can readily reduce them to the 10 −29 e·cm range. Our experiment leads the way in the application of cold molecule techniques to precision measurement and we are well placed to take advantage of recent advances in the preparation [24,25,26] and control [27] of cold molecules to improve our measurement precision. This will allow us to probe for new particle physics at tens of TeV.…”
mentioning
confidence: 99%